The NIH Science of Behavior Change Program: Looking Toward the Future. - Stoeckel, Luke E.; Hunter, Christine; Onken, Lisa; Green, Paige; Nielsen, Lisbeth; Aklin, Will M.; Simmons, Janine M. (Behavior Therapy, 2023)
• SOBC tools aid behavioral interventionists using the experimental medicine approach. • SOBC emphasizes mechanistic insights about malleable behavioral processes. • SOBC intervention development requires measurement of target engagement. • CLIMBR enhances SOBC open science resources and health behavior change research. The National Institutes of Health established the Science of Behavior Change (SOBC) program to promote basic research on the initiation, personalization, and maintenance of health behavior change. The SOBC Resource and Coordinating Center now leads and supports activities to maximize the creativity, productivity, scientific rigor, and dissemination of the experimental medicine approach and experimental design resources. Here, we highlight those resources, including the Checklist for Investigating Mechanisms in Behavior-change Research (CLIMBR) guidelines introduced in this special section. We describe the ways in which SOBC can be applied across a range of domains and contexts, and end by considering ways to extend SOBC's perspective and reach, so as to best promote behavior change linked with health, quality of life, and well-being.